'The pussy ain't worth it, bro': assessing the discourse and structure of MGTOW. Issue 6 (11th May 2020) - Wright, Scott; Trott, Verity; Jones, Callum
ABSTRACT: In the era of networked affordances, misogynistic men's groups have been rapidly growing and have contributed to several physical fatal attacks along with the propagation of gendered online harassment and e-bile. It is thus important to study the organisational structures and communication dynamics of these groups to provide insight into why they have been successful in recruiting members and how they further spread and normalise misogynistic beliefs. One such misogynistic group is MGTOW (Men Going Their Own Way). This study seeks to understand the structure and content of discussion within the forum of the official MGTOW website. To do so, it undertakes a content analysis of comments ( n  = 1012) inspired by Freelon's (2010, 2015 ) multi-norm approach to studying online communication, which draws on the liberal individual, communitarian and deliberative models. It also assesses the broader patterns of commenting ( n  = 628, 745) participation amongst users ( n  = 33, 863). The results suggest that debates on the forum combine elements of each communicative approach and that this reflects a contradiction in their underlying ideology of separation and individualism. In addition, it was found that topics of conversation primarily focused on two topics: women (the majority of which unfold in a misogynistic way) and defining MGTOW – both as a collective identity and a personal journey.